Importancia del microambiente estromal, en particular de la célula madre mesenquimal, y de la célula tumoral en la evolución del cáncer de mama - Martinez, Leandro Marcelo (2015)
This work proposes that the study of breast cancer based on the intrinsic property of tumor cells is insufficient since their microenvironment should be considered. We demonstrated that the bone marrow microenvironment of advanced breast cancer patients creates a favorable pre?metastatic niche for the future progression of bone metastatic cascade. We believe that our results could be useful in designing novel therapies to prevent the development of bone metastasis, as well as, in identifying new indicators of bone metastatic occurrence in these patients. On the other hand, we studied the prognostic significance of tumor microenvironment and tumor cells of primary tumor from early breast cancer patients. We found that the high expression of CD105 in CD34?negative spindle?shaped stromal cells, not associated with the vasculature, as well as, the high expression of TRAIL?R3 and CCR?2 in tumor cells are clear unfavorable prognostic parameters in these patients. Moreover, they are novel biomarkers for identifying patients who are at high risk of developing metastasis. These tools may be highlighted in the clinical?pathological routine as they are easily assessed, accessible and non?invasive.